Spatial frequency of environments and myopia: a systematic review on associated evidence and underlying mechanisms - Li, Dan-Li (2025)
Purpose: Previous animal studies have found a relationship between spatial frequency and myopia. New research in humans suggests that reduced high spatial content of the visual environment may be a contributing factor to myopia development. This study aims to review the literature and elucidate the potential biological mechanisms linking spatial frequency and myopia. Methods: A systematic search was conducted across PubMed and Web of Science databases. The studies published from their inception to August 2024 have explored the connection between spatial frequency and myopia. Only full-text articles in English were included. PRISMA was used for data validity. Results: A total of 13 articles were included in this review, comprising seven animal model studies, four population-based studies, one pictorial analysis, and one study on research design. Epidemiological evidence is comparatively limited and has only begun to emerge in recent years. Mid- to high spatial frequencies were found to play an important role in the emmetropization process of the eye. Low spatial frequencies can increase the risk of myopia incidence. Furthermore, the potential mechanisms of how spatial frequency affects myopia are summarized as visual information processing characteristics, eye accommodation function, eye movements, contrast sensitivity, and relevant molecules involved in the pathway. Conclusion: The evidence suggests that indoor spatial frequency may be related to the development of myopia. Further studies are warranted to understand if the incorporation of changes in indoor environments is helpful in the prevention and control of myopia.